Emerging trends, techniques, and tools for massive open online course (MOOC) management - Queirós, Ricardo 1975- (Advances in educational technologies and instructional design (AETID) book series, 2018)
"This book addresses the difficulties and challenges in the MOOC design, implementation, management and deployment. It focuses on different aspects of the MOOC life-cycle process and explores the impact of new methodologies and frameworks used in the life cycle of a MOOC ranging from well-designed synchronous virtual classrooms to assessment, gamification and collaborative services and tools"...